UK cancer vaccine advance – Recognising and realising opportunities - Charles Craddock; Philip Earwaker; Matthew Fittall; Elisa Fontana; Divya Ganesh; Marco Gerlinger; Qamar Ghafoor; Robert P Jones; Victoria Kunene; Lennard Lee; Rebecca Lee; Siow-Ming Lee; et al. (Cambridge Prisms: Precision Medicine)
Vaccines have revolutionised the field of medicine, eradicating and controlling many diseases. Recent pandemic vaccine successes have highlighted the accelerated pace of vaccine development and deployment. Leveraging this momentum, attention has shifted to cancer vaccines and personalised cancer vaccines, aimed at targeting individual tumour-specific abnormalities. The UK, now regarded for its vaccine capabilities, is an ideal nation for pioneering cancer vaccine trials. This article convened experts to share insights and approaches to navigate the challenges of cancer vaccine development with personalised or precision cancer vaccines, as well as fixed vaccines. Emphasising partnership and proactive strategies, this article outlines the ambition to harness national and local system capabilities in the UK; to work in collaboration with potential pharmaceutic partners; and to seize the opportunity to deliver the pace for rapid advances in cancer vaccine technology.